Spatiotemporal distribution and reproductive biology of the brown croaker (Miichthys miiuy) in the southwestern waters of Korea - Seong Yong Moon; Gun Wook Baeck; Jin Ho Jung; Haeyoung Choi; Changsin Kim; Myung Sung Koo; Jeong-Ho Park (Frontiers in Marine Science)
BackgroundThe brown croaker, Miichthys miiuy, is an economically important fish species in Korean waters. Research on the spawning ecology of M. miiuy in Korea has primarily focused on specimens from the southwestern waters, assessing parameters, such as spawning season and mature body length through histological examination. However, a comprehensive histological analysis across various body sizes during the spawning season is imperative to accurately ascertain these factors, as well as for efficient resource management amidst potential environmental variations. Therefore, this study was undertaken to investigate the spatiotemporal distribution and reproductive biology of M. miiuy in the southwestern waters of Korea.MethodsMonthly changes in gonadal maturity stages, gonadosomatic index (GSI), egg diameter, and fecundity were analyzed. Additionally, total length at sexual maturity at 50%, 75%, and 97.5%, as well as the sex ratio, were determined.ResultsM. miiuy, captured using offshore gillnets and stow nets, exhibited a seasonal migration pattern: a winter presence near Jeju Island, followed by a northward movement in spring, a summer shift to the shallow waters of Shinan, and an autumnal migration to the waters around Jeju Island for overwintering. The overall female-to-male sex ratio was 1:0.8. GSI values peaked in September and August for both sexes; however, microscopic analysis of gonadal tissue revealed a spawning period from July to September 2023, with the primary spawning season for the entire population occurring in August and September. The fork length at 50% maturity was 57.4 cm for females and 54.6 cm for males.ConclusionOverall, these results suggest an earlier shift in the spawning period of brown croakers in the southwestern waters of Korea compared to past observations. This shift is potentially attributable to higher water temperatures, increased resource levels, and alterations in the species composition of major prey items in the spawning grounds. Further research is imperative for a comprehensive understanding of the factors influencing the reproductive ecology of this important fish species.